Radio Luminosity Function of Flat-spectrum Radio Quasars - Mao, Peiyuan (2017)
We present the radio luminosity function (LF) of flat-spectrum radio quasars (FSRQ), using the the largest and most complete sample to date. Cross-matching between the FIRST 20 cm and GB6 6 cm radio surveys, we find 638 flat-spectrum radio sources above 220 mJy at 1.4 GHz; of these, 327 are are classified and verified using optical spectroscopy data, mainly from Sloan Digital Sky Survey Data Release 12. We also considered flat-spectrum radio sources that lack both literature references and optical spectroscopy, and we identified 12 out of the 43 such sources to potentially be FSRQs, using their WISE colors. From the fully identified sample of 242 FSRQs, we derived the radio LF and cosmic evolution of blazars at 1.4 GHz, finding good agreement with previous work at 5 GHz. The number density of FSRQs increases dramatically to a redshift of z ∼ 2 and then declines for higher redshifts. Furthermore, the redshift at which the quasar density peaks is clearly dependent on luminosity, with more luminous sources peaking at higher redshifts. The approximate best-fit LF for a luminosity-dependent evolutionary model is a broken power-law with slopes ∼0.7 and ∼1.7 below and above the break luminosity, log L1.4 ∼ 43.8 erg s-1, respectively.